Facing China as a New Global Superpower
XI, 279 p. 11 illus., 1 illus. in color.
Keywords: This book brings together diverse perspectives from the newest generation of scholars from Canada and China to better understand China in the 21st century. It examines China's socio-political structure, its particular relationship with Canada, and interaction with the international community; and discusses how to overcome the ideological differences between the two countries to establish positive and sustainable Canada-China bilateral relations for the future. Importantly, the perspectives are from young authors, with a different relationship to China (and Canada) than more established authors. This compilation helps breathe new life into the study of Sino-Canada relations from both countries, and to reassess and re-frame issues related to China in the 21st century.